Efficacy of papain in reducing soft tissue swelling- a case report - Devaraj, Navin Kumar (Rwanda Health Communication Center, 2020)
Papain or serratiopeptidase, a cysteine protease enzyme present in papaya, has been used for centuries as an anti-inflammatory drug. Now in modern medicine, it is being propagated as an anti-swelling medication. However, reports are mixed on the efficacy of papain in reducing swelling. This case report look at the success of papain in reducing the size of olecranon bursitis in a 50-year-old patient The amazing reduction of the size of the bursitis in just two weeks without any surgical interventions might just swing the pundits to the positive direction of its benefit As evidence on the usage of this drug has been equivocal., this case report can hopefully shed some wonderful benefit of this drug.